2015
DOI: 10.1002/mus.24709
|View full text |Cite
|
Sign up to set email alerts
|

How electrodiagnosis predicts clinical outcome of focal peripheral nerve lesions

Abstract: This article reviews the electrodiagnostic (EDX) prognostic factors for focal traumatic and nontraumatic peripheral nerve injuries. Referring physicians and patients often benefit from general and nerve-specific prognostic information from the EDX consultant. Knowing the probable outcome from a nerve injury allows the referring physician to choose the best treatment options for his/her patients. Nerve injuries are variable in their mechanism, location, and pathophysiology. The general effects of the injuries o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 73 publications
1
40
0
3
Order By: Relevance
“…23 One should not delay any exploration of an injured nerve, if there is a strong indication for exploration, by waiting for an electrophysiological examination. Intra-operative nerve conduction and electrical stimulation of individual nerve branches or fascicles can be of great help in deciding how a nerve reconstruction of a nerve injury in continuity should be done since some intact fascicles can be spared if functional axons are located.…”
Section: Cellular Reactions After Nerve Injurymentioning
confidence: 99%
“…23 One should not delay any exploration of an injured nerve, if there is a strong indication for exploration, by waiting for an electrophysiological examination. Intra-operative nerve conduction and electrical stimulation of individual nerve branches or fascicles can be of great help in deciding how a nerve reconstruction of a nerve injury in continuity should be done since some intact fascicles can be spared if functional axons are located.…”
Section: Cellular Reactions After Nerve Injurymentioning
confidence: 99%
“…Thirteen of 16 articles demonstrated an additive predictive value of EDx. Prognostication of NBPP depends on extent, severity of the lesion, recruitment in muscles supplied by the damaged nerve, and the individual speed of recovery . EDx should provide this information accurately.…”
Section: Discussionmentioning
confidence: 99%
“…EDx can help to distinguish between these lesions. Comparing distal and proximal CMAP gives an estimation of the conduction block. In the case of axonal loss, there are timing limitations for using CMAP: using this measure too early or too late can overestimate the number of viable axons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is fundamental to determine the amplitude of the CMAP in order to quantify the number of muscle fibers which are actually reinnervated (Robinson, ). In this study, the amplitude of CEE group was greater than that observed in the PEE group, possibly because a greater number of myelinated axons regenerated in the CEE group and consequently reinnervated a greater number of muscle fibers.…”
Section: Discussionmentioning
confidence: 99%